Groupthink: Collective delusions in organizations and markets - Roland Bénabou (Institute for the Study of Labor (IZA), 2013)
This paper investigates collective denial and willful blindness in groups, organizations and markets. Agents with anticipatory preferences, linked through an interaction structure, choose how to interpret and recall public signals about future prospects. Wishful thinking (denial of bad news) is shown to be contagious when it is harmful to others, and self-limiting when it is beneficial. Similarly, with Kreps-Porteus preferences, willful blindness (information avoidance) spreads when it increases the risks borne by others. This general mechanism can generate multiple social cognitions of reality, and in hierarchies it implies that realism and delusion will trickle down from the leaders. The welfare analysis differentiates group morale from groupthink and identifies a fundamental tension in organizations' attitudes toward dissent. Contagious exuberance can also seize asset markets, generating investment frenzies and crashes.
Keywords: D03; D23; D53; D83; D84; E32; G01; G14; Z1; 330; groupthink; organizational culture; overconfidence; optimism; morale; market exuberance; manias speculative bubbles; market crashes; financial crises; toxic assets; wishful thinking; cognitive dissonance; cognitive biases anticipatory feelings; resolution of uncertainty; psychology